Low friction in self-mated silicon carbide tribosystem using nanodiamond as lubricating additive in water - Xudong Wang; Hirotsuna Sato; Koshi Adachi (Friction, 2020)
Abstract Nanodiamond particles (NDPs) have been considered as a potential lubricant additive to various tribological applications, such as water lubrication systems. In this study, the tribological properties of silicon carbide (SiC) lubricated by NDPs dispersed in water are investigated utilizing the ball-on-disk tribometer. It is found that the slight addition of NDP to water (i.e., 0.001 wt%) can distinctly accelerate the running-in process, which is necessary to achieve a friction coefficient (μ) as low as 0.01. This study also discusses two NDP functional terminations —hydroxyl and carboxyl. It is demonstrated that the use of carboxyl-terminated NDP over a wide range of concentration (0.001 wt%–1 wt%) yields a low friction force. In contrast, the ideal effective concentration of hydroxyl-terminated NDP is considerably limited because agglomeration in this material is more probable to occur than in the former. Meanwhile, when utilizing NDPs, the input friction energy (P in, defined as the product of sliding speed and applied load) is found to have an essential function. Several sliding tests were implemented at various P in values (50–1,500 mW) using carboxyl-terminated water-dispersed NDPs. It was observed that the μ and wear decreased with increasing P in when 200 mW < P in < 1,500 mW. However, when P in < 200 mW, low friction with high wear occurs compared with the resulting friction and wear when pure water is used.